Azov Battalion - History & Symbols - Mark Felton Productions (2022)
The Ukrainian Army's Azov Battalion is controversial due to its use of symbols associated with the Waffen-SS. In this video, we will examine the unit's history and what those symbols mean. Dr. Mark Felton is a well-known British historian, the author of 22 non-fiction books, including bestsellers 'Zero Night' and 'Castle of the Eagles', both currently being developed into movies in Hollywood. In addition to writing, Mark also appears regularly in television documentaries around the world, including on The History Channel, Netflix, National Geographic, Quest, American Heroes Channel and RMC Decouverte. His books have formed the background to several TV and radio documentaries. More information about Mark can be found at: https://en.wikipedia.org/wiki/Mark_Fe... Visit my audio book channel 'War Stories with Mark Felton':    • One Thousand Miles to Freedom Help support my channel: https://www.paypal.me/markfeltonprodu... https://www.patreon.com/markfeltonpro... Disclaimer: All opinions and comments expressed in the 'Comments' section do not reflect the opinions of Mark Felton Productions. All opinions and comments should contribute to the dialogue. Mark Felton Productions does not condone written attacks, insults, racism, sexism, extremism, violence or otherwise questionable comments or material in the 'Comments' section, and reserves the right to delete any comment violating this rule or to block any poster from the channel. Credits: US National Archives; US Department of Defense; Carl Ridderstrale; Inkscape'r; Alex Kaplaux; Qypchak; Cherubino; ZDF